Rádio em tempos de downloads: a reconfiguração do rádio FM musical diante das novas tecnologias da informação e da comunicação - Chagas, Jefferson Mickselly Silva (2010)
The aim of this paper is to discuss the challenges which the radio media has faced towards the reconfiguration of the musical circuit in cyber culture. The FM stations have their programming mostly based on the air playing of songs. These stations have been acting for decades as main musical mediator, serving as inspiration for the phonographic industry and also giving visibility to artists and influencing in the making of their repertoires. However, today the role of the FM stations have been questioned and even pointed as the reason for a crisis in the radio industry due to the release of new music players and the high achievement of new listening habits developed from the digital media. The central debate of this paper is related to the paradigm of the technological substitution in which the radio with its top-down system would be slowly overpowered by the internet bottom-up system. Two Brazilian stations were investigated regarding their media strategies towards their approach to the digital technologies; Oi FM which allows the listener to receive their airplay through the cell phone and MPB FM which have been constantly present in social network sites.